2023
DOI: 10.3389/fonc.2023.1151871
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of global research trends and prospects on platinum-resistant ovarian cancer: a bibliometric analysis

Abstract: BackgroundIn the last decades, growing attention has been focused on identifying effective therapeutic strategies in the orphan clinical setting of women with platinum-resistant ovarian cancer (PROC), generating thousands of original articles. However, the literature involving bibliometric analysis of PROC has not been published yet.ObjectiveThis study hopes to gain a better understanding of the hot spots and trends in PROC by conducting a bibliometric analysis, as well as identify potential new research direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…It is a text mining method based on artificial intelligence algorithms that assesses the interrelationships and impacts of publications and uses mathematical and statistical techniques to identify and organize knowledge structure ( 12 ). It not only provides quantitative statistical analysis of publications in a specific field but also helps readers understand the development of the discipline and visualize the frontiers through mapping ( 13 ). Bibliometrics plays a crucial role in biomedical disciplines like inflammation, genetics, and cancer, aiding in illness treatment and the development of clinical guidelines ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a text mining method based on artificial intelligence algorithms that assesses the interrelationships and impacts of publications and uses mathematical and statistical techniques to identify and organize knowledge structure ( 12 ). It not only provides quantitative statistical analysis of publications in a specific field but also helps readers understand the development of the discipline and visualize the frontiers through mapping ( 13 ). Bibliometrics plays a crucial role in biomedical disciplines like inflammation, genetics, and cancer, aiding in illness treatment and the development of clinical guidelines ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer is one of the most lethal malignancy of the female reproductive system worldwide (Duan et al 2023). Due to the lack of early diagnosis methods, more than 70% of patients reach advanced stages at the time of diagnosis (Dochez et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This methodology allows not only the evaluation of research quality but also the identification of developing research trends and the prediction of possible future research directions ( 11 , 12 ). Previous studies have utilized bibliometric analysis to examine prominent research topics and studies concerning OC ( 13 15 ). Duan’s research revealed that platinum-resistant OC is primarily focused on identifying populations that can benefit from immunotherapy alongside the practical implementation of immune checkpoint inhibitors ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have utilized bibliometric analysis to examine prominent research topics and studies concerning OC ( 13 15 ). Duan’s research revealed that platinum-resistant OC is primarily focused on identifying populations that can benefit from immunotherapy alongside the practical implementation of immune checkpoint inhibitors ( 13 ). Baghban’s findings indicated an increasing trend in the research of extracellular vesicles and epithelial ovarian cancer ( 14 ).…”
Section: Introductionmentioning
confidence: 99%